A novel aspect of functionalized graphene quantum dots in cytotoxicity studies. (December 2019) - Mehrdad-Vahdati, Bahare; Pourhashem, Sepideh; Sedghi, Mosslim; Vaezi, Zahra; Shojaedin-Givi, Behnaz; Rashidi, Alimorad; Naderi-Manesh, Hossein
Abstract: Graphene quantum dots (GQDs) represent a new generation of graphene-based nanomaterials with enormous potential for use and development of a variety of biomedical applications. However, up to now little studies have investigated the impact of GQDs on human health in case of exposure. GQDs were synthesized from citric acid as carbon precursor by hydrothermal treatment at 160 °C for 4 h. The synthesized GQDs showed strong blue emission under UV-Irradiation with fluorescence quantum yield of 9.8%. The obtained GQDs were further carbonized, activated and functionalized by nitric acid vapor method. Nitrogen adsorption/desorption isotherms were used to analyze the surface area and porous structures of GQDs. The results revealed that compared to GQDs, the specific surface area of functionalized graphene quantum dots (fGQDs) has been increased from 0.0667 to 2.5747 m 2 /g and pore structures have been enhanced significantly. The potential cytotoxic effect of GQDs, fGQDs and GO suspensions was evaluated on HFF cell line using MTT assays and flow cytometry method after 24 h incubation. We have for the first time demonstrated that by carbonization, activation and functionalization of GQDs they still showed cytocompatible properties. We observed excellent biocompatibility of GQDs and fGQDs at low concentrations. Moreover, the results suggested that modification of GQDs yields product suspensions with high surface area, enhanced pore volume and loading capacities. Thus, fGQDs represent an attractive candidate for further use in drug delivery systems and bio-imaging application. Graphical abstract: Novel modified graphene quantum dots prepared from natural, eco-friendly and biocompatible materials. Unlabelled Image Highlights: Blue luminescent graphene quantum dots were modified by acid vapor method. The modified graphene quantum dots showed very high specific surface area with enhanced pore structures. The functionalized graphene quantum dots revealed high loading capacities. The excellent biocompatibility was confirmed toward HFF cells at low concentrations.